Meningkatkan Pemahaman Konsep Peserta Didik dalam Pembelajaran IPS (Materi Sejarah) Melalui Media Power Point di SMP Negeri 16 Kota Bogor - Gunarti Sukriyatun (Universitas Negeri Yogyakarta, 2016)
The purpose of this research is to know the improvement of quality learning process and learning outcomes of Social Sciences in class 7.6 through media Power Ponit. The population of this research is the grade seventh of Yunior High School are consisted 36 students, there are 17 female and 19 male students. The implementation of this research at mid semester in 2010/2011. The result of this research showed in the first cycle get the value 73,89 or completeness study of 97,22% while in the second cycle get the value 80,83 or completeness study of 100%, it means that the research is successfully. Meanwhile, the assessment of quality in learning on the first cycle is 77,50% and the second cycle is 99,17%. In the other hand, the observation result of students behavior are showed an increasing with the value of the first cycle is 69,44% and in the second cycle is get the value 100%. Based on the result of this research above, it can be conclude that the implementation of Media Power Point can improve the result in cognitive learning of Social Sciences. In addition it can improve the quality of learning and participation with students’ behavior. Keywords: Results of learning, Media Power Point